2010
DOI: 10.1111/j.1755-3768.2009.01554.x
|View full text |Cite
|
Sign up to set email alerts
|

Corneal hysteresis measured with the Ocular Response Analyzer® in normal and glaucomatous eyes

Abstract: ABSTRACT.Purpose: To identify differences in corneal hysteresis (CH) and central corneal thickness (CCT) between healthy and glaucomatous patients. Methods: Retrospective observational study. One hundred and thirty-three eyes of 75 healthy and 58 glaucomatous patients were included. CH was measured in each patient using Ocular Response Analyzer. CCT was determined by ultrasonic pachymetry. For each patient, one eye was randomly selected. We used a Student t-test to search for significant differences between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
78
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 23 publications
(40 reference statements)
2
78
0
3
Order By: Relevance
“…1,23 Conversely, it has been suggested that low CH might be expected to increase the risk for developing glaucomatous optic neuropathy, possibly due to reduced capacity of the eyewall to dampen IOP spikes 23,24 and/or reduced ability of optic nerve structures to suitably respond to IOP fluctuations. 1,25,26 This premise is supported by several studies, which indicate that eyes with POAG exhibit lower CH compared with normal eyes [1][2][3][12][13][14][15][16] and eyes with OH. 1,12 In addition, lower CH has been linked to both glaucoma progression 17,18 and severity.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…1,23 Conversely, it has been suggested that low CH might be expected to increase the risk for developing glaucomatous optic neuropathy, possibly due to reduced capacity of the eyewall to dampen IOP spikes 23,24 and/or reduced ability of optic nerve structures to suitably respond to IOP fluctuations. 1,25,26 This premise is supported by several studies, which indicate that eyes with POAG exhibit lower CH compared with normal eyes [1][2][3][12][13][14][15][16] and eyes with OH. 1,12 In addition, lower CH has been linked to both glaucoma progression 17,18 and severity.…”
Section: Introductionsupporting
confidence: 65%
“…[1][2][3][12][13][14][15][16] Accordingly, identification of a specific CH value that provides good sensitivity and specificity for differentiating eyes with and without glaucoma has been elusive. Because it is a relatively dynamic variable, however, adjusting CH for the factors that influence its variability potentially may foster a more robust relationship between CH and clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…lower CH (Abitbol et al 2010). There is also an association between low CH and the progression of glaucoma (Congdon et al 2006).…”
Section: Introductionmentioning
confidence: 94%
“…[3][4][5][6] Abitbol et al in 2009 provided the ground work for establishing population values for CH and CCT. They found healthy eyes with a mean age of 61.44 years to have a mean CH of 10.46 ± 1.6 and a mean CCT of 560.2 ± 36.3.…”
Section: Introductionmentioning
confidence: 99%